COMPARATIVE LAW AGAINST ONLINE PROSTITUTION ACCORDING TO INDONESIAN AND DUTCH LAW - Muhammad Akbar Ridho; Yati Nurhayati (Al-Adl : Jurnal Hukum, 2022)
Prostitution is a complex problem. Hence it requires serious and comprehensive attention and handling from some aspects – moral, social, cultural, legal, or norms, etc. The legal norms from various different countries, including Indonesia, categorize prostitution as an illegal action, whereas others are silent with some exceptions. One of the countries legalizing prostitution is the Netherlands. When the Dutch government legalized prostitution in 2000, it was to protect women by giving them work permits. This research focuses on answering how the Comparison of Criminal Law Policies against Online Prostitution in Indonesia and the Netherlands is. The method used was normative legal research. The results showed that Indonesia prohibits prostitution even though the crime uses the relevance between the Criminal Code and certain laws as there is no specific legal policy regarding online prostitution in Indonesia. Meanwhile, the Dutch legal policy in responding to the online prostitution issue, legalizes prostitution with the terms and conditions of the Bibob law.